Da literacia ou de uma narrativa sempre imperfeita de outra identidade pessoal - Maria da Graça Pinto Castro (Universidade do Minho, 2002)
During the last years, among us, the word literacy has been highly used, and as for other labels, which circulate in our society, it doesnt seem that we have enough knowledge to speak about it with the necessary confidence. Therefore, with this text I intend to show how literacy is open not only to different approaches but also to a plural reading as a result of the constant changes of society. As it can be anticipated from the title, the literacy levels in several domains that each one demonstrates correspond inevitably to a form of personal identity. It happens, however, that this identity is neither definitive nor can be assumed without an active participation. From each citizen it is expected a permanent investment since it is a process in which he is continually engaged; from the society to which he belongs it is expected the enough openness to updating this particular narrative around personal identity that more than another else can be characterised as being always unaccomplished.